In-hospital and late outcome of rescue versus primary percutaneous coronary intervention in patients with ST-segment elevation myocardial infarction - hossein vakili; Roxana Sadeghi; Solmaz Borjian; Naser Kachoueian (International Journal of Cardiovascular Practice, 2016)
Introduction: Despite high technical success of rescue Percutaneous Coronary Intervention (PCI) and also its significant impact on left ventricular function, the therapeutic outcome of this PCI technique in comparison with primary PCI for coronary reperfusion has remained uncertain. The present study aimed to conduct a comparative analysis of early and long-term results of patients with ST-Elevation Myocardial Infarction (STEMI), who had undergone primary or rescue PCI.Methods: One hundred and twenty-nine consecutive patients with the diagnosis of STEMI, who underwent primary PCI (n = 107) or rescue PCI (n = 22) from April 2012 to September 2013 were retrospectively included. In addition to early assessment of procedural consequences, the patients were followed-up to assess and compare long-term mortality and major adverse cardiovascular events.Results: Comparing in-hospital consequences of the two rescue PCI and primary PCI procedures showed no significant differences in in-hospital mortality (9.5% vs. 3.7%, P = 0.255), total hospital stay (6.32 ± 2.24 days vs. 6.61 ± 3.43 days, P = 0.720) and also in early procedural complications. Long-term death was found only in 1.9% of patients in the primary group and none of the patients in the rescue group (P = 0.999). There was also no difference in the prevalence of late stent thrombosis between the two groups. However, the in-hospital Left Ventricular Ejection Fraction (LVEF) was lower in the rescue PCI group vs. primary PCI group (36.82 ± 11.19 vs. 43.48 ± 9.14, P = 0.014), but after six months, LVEF was similar between the two groups (41.05 ± 9.57 vs. 44.29 ± 10.35, P = 0.082).Conclusions: Our study showed no difference in early and late procedural outcome between the primary and rescue PCI techniques in STEMI patients, but LVEF had better improvement in the rescue PCI group.